Uji Laboratorium: Analisis Berat Lumpur Pemboran Pada Sumur Can - Wahyuni, Viola Sri; Fathan, Muhammad Rizqie; Ulfah, Baiq Maulinda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Drilling mud plays an important role in maintaining well stability, especially since each trajectory faces different lithological and formation pressure issues. On the 36" (conductor) trajectory, the main challenge is shallow pressure that has the potential to cause surface gas, so 8.83 ppg mud is used as a solution to withstand this pressure. The 26“ (top hole) trajectory faces swelling clay issues, so mud with a density of 10.7 ppg is selected to suppress clay expansion. In the 17 ½” (intermediate 1) trajectory, the main problem stems from reactive shale that is prone to collapse, so mud with a weight of 10.9 ppg is designed to maintain hole stability. In the 12 ¼” (intermediate 2) section, the presence of a high-pressure fracture zone required heavier mud, namely 12.9 ppg, to control formation pressure. Meanwhile, the 8 ½” (production hole) section faced the most critical conditions with the risk of HPHT, kick, and lost circulation, so mud with a density of 14.9 ppg was the best solution. The objective of this study is to obtain the right mud formula for each track by utilizing barite as the main weighting material, so that the mud weight can be adjusted to field requirements.